The severity and manifestations of psychopathological symptoms in cosmetological patients - Юдін, Михайло Анатолійович (ScienceRise: Medical Science, 2016)
The significant prevalence of psychic pathology among patients of the medical sphere, including medical cosmetology, raises a question on organization of medical-psychological help for this profile of patients/clients. Aim of research – to detect the severity and manifestations of psychopathological symptomatology in cosmetological patients. Contingent and methods of research. In testing participated 286 жінок, who asked for cosmetological help. The interrogated were divided into 3 groups on the base of self-attitude criterion: 1 group included persons with disharmonic type and tendency to the lowered self-concept (G1, n=108), 2 group2 – with harmonic type (G2, n=96) and 3 group – with disharmonic one with tendency to the heightened self-concept (G3, n=82). The determination of severity of psychopathological symptomatology was carried out by SCL-90-R method. Results. In women, asked for cosmetological help, was the different level of psychopathological symptomatology depending on type of self-attitude. The features of psychopathological status of patients with disharmonic type of self-attitude with inclination to the low self-concept were the higher levels of psychic distress and its severity, psychopathological symptomatology was presented by the anxious-depressive, anxious-phobic, obsessive-compulsive manifestations, interpersonal sensitivity, transformation of psychic conflicts into somatic sphere, in women with disharmonic type of self-attitude with inclination to the heightened self-concept – intensive psychic distress that was manifested in psychopathological anxiety, somatization, hostility and mistrust as to surrounding people. Psychopathological status of women with harmonic type of self-attitude is characterized with the lower levels of psychopathological manifestations, reaction to the psychic stress such as monosymptoms of affective or anxious spectrum, somatization. Conclusions. Women, asked for cosmetological help, form the group that is heterogenic by psychological characteristics that must be taken into account at giving medical and psychological help. Patients with disharmonic type of self-attitude, especially with inclination to the low self-concept, form the risk group as to psychological health and need medical-psychological help